"The Effect of Cold Compresses on Reducing the Pain Scale of Cannulation" In Chronic Kidney Failure Patients Undergoing Hemodialysis in Jakarta Cempaka Putih Islamic Hospital” - Delia Amelia; Bahreni Yusuf; Hendik Wicaksono (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Cannulation pain is a common problem in chronic kidney failure patients undergoing hemodialysis which impacts the patient's quality of life. Cold compress therapy is a non-pharmacological therapy to reduce pain through vasoconstriction mechanisms and modulation of nerve activity. This study aims to determine the effect of cold compresses on reducing the cannulation pain scale in chronic kidney failure patients undergoing hemodialysis at the Jakarta Islamic Hospital Cempaka Putih. Method: Using a Pre-Experiment with a One Group Pretest and Posttest Design research design with a sample of 18 respondents. There was a decrease in the pain scale with pretest pain values there were 9 respondents with mild pain and 9 other respondents with moderate pain, after being given cold compress therapy, 7 respondents did not experience pain and 11 respondents had a mild pain scale with p-value 0.001 <0.05. There is an effect of cold compresses on reducing the cannulation pain scale in chronic kidney failure patients undergoing hemodialysis at the Jakarta Islamic Hospital Cempaka Putih